The false analogy between refusal-renunciation of treatments and physician-assisted suicide. Bioethical considerations about the Constitutional Court Ordinance No. 207/2018 - Da Re, Antonio (Medicina e Morale, 2019)
The paper provides some bioethical considerations that are particularly lacking within Ordinance n. 207/2018 issued by the Constitutional Court. With reference to the case of Fabiano Antoniani, better known as DJ Fabo, who requested and subsequently committed assisted suicide after being accompanied by Marco Cappato to Switzerland, the ordinance deals with the dubious constitutional illegitimacy of Article 580 of the Italian Criminal Code. On the one hand, the paper brings attention to the Constitutional Court's thesis that criminal provision on assisted suicide is not incompatible with the Constitution. On the other hand, it criticizes how the Court justifies medical aid to suicide - albeit in relation to certain exceptional situations. This justification is based on the erroneous assumption that there are not significant differences between refusal-renunciation of treatments and physician-assisted suicide. On the basis of this assumption, the Court has come up with the highly questionable proposal of modifying the recent law, n. 219/2017, titled "Norme in materia di consenso informato e di disposizioni anticipate di trattamento". The paper then argues that Ordinance n. 207/2018 is characterized by the logical fallacy of false analogy. The fallacy is developed in four phases in which different concepts and situations are erroneously equalized. The four phases concern 1) the binomial of killing-letting die; 2) the meaning of death; 3) the meaning of drug treatment; 4) the value of the patient-physician relationship.